2003
DOI: 10.2337/diacare.26.1.187
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Birth Weight to Fasting Insulin, Insulin Resistance, and Body Size in Adolescence

Abstract: OBJECTIVE -A relationship between birth weight and the insulin resistance syndrome has been reported in adults but has not been defined in adolescents.RESEARCH DESIGN AND METHODS -Data were analyzed in 296 children (132 girls and 164 boys) mean age 15.0 Ϯ 1.2 years who had euglycemic insulin clamp studies (intravenous administration of 1 mU ⅐ kg -1 ⅐ min -1 of insulin balanced by a variable infusion of 20% glucose to maintain blood glucose at 100 mg/dl). Insulin sensitivity (M LBM ) was determined by glucose u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
54
1
15

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 27 publications
10
54
1
15
Order By: Relevance
“…insulin resistance (21). Birth weight was strongly related to maternal weight gain in accordance with results of other studies of both normal-weight and obese women (3,22).…”
Section: Statistical Analysessupporting
confidence: 90%
“…insulin resistance (21). Birth weight was strongly related to maternal weight gain in accordance with results of other studies of both normal-weight and obese women (3,22).…”
Section: Statistical Analysessupporting
confidence: 90%
“…Subsequently, several investigations reported that low birth weight followed by excessive weight gain in childhood led to insulin resistance and hypertension in adults (7)(8)(9). The relationship between low birth weight and increased risk of insulin resistance or type 2 diabetes mellitus has also been reported in children (10,11). We also reported a negative correlation between birth weight and systolic blood pressure in children aged 3 years (12).…”
Section: Introductionsupporting
confidence: 66%
“…Several studies have reported an inverse association between BW and abdominal or truncal adiposity in children and adults (5,(14)(15)(16)(17)(18). However, other studies have shown a U-shape relation between BW and abdominal adiposity (8,17,19). These inconsistencies may be partly explained by the variety of methods used to assess abdominal adiposity.…”
Section: Introductionmentioning
confidence: 59%